NILAI PENTING PENGEMBANGAN KOPI DI KABUPATEN TEMANGGUNG - Fatjrin, Ainin Nur; Swasono, Didiet Heru; Sambodo, Reo (Prosiding Seminar Nasional Mini Riset Mahasiswa, 2025)
Coffee is one of the main agricultural commodities in Indonesia. Temanggung Regency has a long history of coffee cultivation and has become one of the pillars of the local economy. This study aims to determine the social, economic, and environmental impacts, the role of technology in improving coffee production and quality, and the efforts to empower local coffee farmers to enhance production yields and the competitiveness of Temanggung coffee products. This research was conducted from September 3 to November 3, 2024, in Temanggung Regency. The data required for this study includes both primary and secondary data. The data collection technique used purposive sampling and snowball sampling methods to select respondents. The type of research conducted is qualitative (survey-based). The development of coffee in Temanggung has encouraged youth participation in the coffee business, particularly in the coffee derivative industry. This indicates a positive social change with increasing awareness among the younger generation about local potential. Arabica and Robusta coffee have a significant impact on the community's economy. The Temanggung Regency Government actively provides assistance to Arabica (75%) and Robusta (47.5%) coffee farmers every 36 days, covering training, post-harvest management, and plant maintenance. This assistance enhances farmers' ability to utilize technology for coffee productivity.All Arabica and Robusta coffee farmers in Temanggung actively carry out routine maintenance, such as pruning, precise fertilization, and pest control. This maintenance ensures high-quality coffee beans, making them competitive in the market.Key : Coffee, Economy, Social, Environment, Empowerment